Comparison of regional and general anesthesia for retrograde intrarenal surgery: a systematic review and meta-analysis - Ho, Yen; Wen, Yu-Ching; Lee, Liang-Ming; Lin, Ke-Hsun; Hsiao, Chi-Hao; Syu, Syuan-Hao; Lai, Benjamin Chung-Howe; Chung, Cho-Hsing; Lin, Yung-Wei (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the effectiveness and safety of retrograde intrarenal surgery (RIRS) for urolithiasis under different anesthesia methods based on current evidence.Materials and methodsIn March 2022, systematic research was conducted using the databases PubMed, Embase, Google Scholar, and the Cochrane Library to compare outcomes of RIRS with regional anesthesia (RA) or general anesthesia (GA) through randomized controlled trials (RCTs) and observational studies. Data analysis was performed using the comprehensive meta-analysis software version 3.ResultsEight RCTs and one retrospective study, involving a total of 2,111 individuals, were included in the current review. Pooled data revealed no significant statistical differences in RIRS under RA compared to RIRS under GA in terms of stone-free rate (SFR) [odds ratio (OR) = 1.02, p = 0.94], operating duration [weighted mean difference (MD) = −0.04, p = 0.88], length of hospital stay (MD = −0.05, p = 0.63), postoperative first-day visual analog scale score (MD = 0.18, p = 0.30), and complication rates (OR = 0.83, p = 0.20). However, one of the RCTs reviewed showed a potential negative effect of GA on the renal function at the operative site. Maneuverability and accessibility were found to be significantly better with SA and sedation than with GA. Additionally, the cost of GA was noted to be significantly higher than that of RA, according to more than one RCT.ConclusionThe present study revealed that RIRS under RA is not inferior in effectiveness and safety compared to that under GA, in terms of SFR, operating time, length of hospital stay, postoperative pain scores, and complication rates. Moreover, RA may offer better long-term renal function preservation and be more cost effective than GA. To improve maneuverability and accessibility for operators, we suggested that RA with sedation could be a suitable alternative with careful patient selection.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023463411, identifier: CRD42023463411.